PERKEMBANGAN PENERBITAN DAN PUBLIKASI KARYA SASTRA DI BANGKALAN MULAI MASA 60-AN SAMPAI DENGAN MASA MUTAKHIR - Muhri, Muhri; Masnawati, Eli (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
This research aims (1) to describe the publishing of local literary work of Bangkalan from the 1960s till now and (2) to describe background and factors of publishing local literary work of Bangkalan from the 1960s till now. Methods of collecting data in this research are document study and interview. Document study was used to collect data for (1) and interview for (2). Analysis results that local literary work of Bangkalan, though written since the 1960s, was published firstly by 1998. It was one of some agenda in Temu Sastrawan Jawa dan Bali held by Lingkar Sastra Junok (Junok Literary Circle). The factors behind the publishing of literary work in Bangkalan including three things: first, publishing as part of the art (literary) event, second, publishing for (self)-conservation and third, publishing for a competition event.